Enhanced spatial navigation skills in sequence-space synesthetes. (September 2020) - van Petersen, Eline; Altgassen, Mareike; van Lier, Rob; van Leeuwen, Tessa M.
Abstract: Individuals with sequence-space synesthesia (SSS) perceive sequences like months, days and numbers in certain spatial arrangements. Several cognitive benefits have been associated with SSS, such as enhanced mental rotation, more vivid visual imagery and an advantage in spatial processing. The current study aimed to further investigate these cognitive benefits, focusing on spatial navigation skills, to explore if their enhanced sensitivity to spatial relations is reflected in enhanced navigational performance. Synesthetes were distinguished from controls by means of a questionnaire, a consistency test and drawings. A virtual Morris Water Maze (MWM) task with two allocentric and two egocentric navigation conditions was used to assess spatial navigation abilities. For the allocentric tasks, participants had to use object cues to find a hidden platform and for the egocentric tasks, they had to use their own position as a reference. Results showed that synesthetes performed significantly better compared to controls on the allocentric and egocentric tasks that reflected real life situations more accurately. However, this significant result was only found for the time taken to find the platform and not for the length of the path that was taken. In exploratory analyses, no significant relations were found between task performance and the specific features of the manifestation of each individual's synesthesia. Our hypothesis that synesthetes with the ability to mentally rotate their spatial arrangements would perform better on the allocentric task was not confirmed. Results add to the growing body of literature concerning the cognitive benefits of SSS and are consistent with the possibility that enhanced spatial navigation skills emerge from generally enhanced visuospatial abilities in SSS.